HUMAN RIGHTS EDUCATION AND SOCIAL MOVEMENTS: STRUGGLES AND RESISTANCES - da Silva, Ana Claudia Lima; de Santana, Gildo Ribeiro (Seven Editora, 2025)
The article aims to identify, in a critical way, the contribution of Human Rights Education (HRE) and social movements to the construction of public policies and their developments in the context of the development of citizenship and human dignity. In particular, the ways in which the relations between social movements and the State have been addressed, with regard to the violation of human rights. Methodologically, it is a qualitative research, with bibliographic and documentary procedures. It is concluded that the struggle for the realization of rights through social mobilizations occurs with advances and setbacks, the need for effective actions is evident. However, the formation of the individual is shown as a form of resistance, so that social agendas can be put into effect as instruments of protection of human rights already conquered and those that will arise. DOI: https://doi.org/10.56238/sevened2025.021-006